A case report of advanced heart failure refractory to pharmacological therapy who was successfully recovered by combinatory usage of cardiac resynchronizing therapy, Impella and MitraClip. Issue 6 (5th November 2020) - Sobajima, Mitsuo; Fukuda, Nobuyuki; Ueno, Hiroshi; Kinugawa, Koichiro
Abstract: Background : The safety and efficacy of MitraClip for advanced heart failure (HF) patients who are inotrope-dependent or mechanically supported are unknown. Case summary : The patient was a 71-year-old man diagnosed as dilated cardiomyopathy in 2003. He was admitted due to worsening HF in January 2019 and became dependent upon intravenous infusion of inotropes. During the 8-month hospitalization, his haemodynamics were relatively static with bed rest and continuous inotropes, but he was definitely dependent on them. Our multidisciplinary team decided to perform both cardiac resynchronization therapy (CRT) and MitraClip under Impella support. First, Impella was inserted from left subclavian artery. After a week, CRT was implanted from right subclavian vein, and the QRS duration of electrocardiogram became remarkably narrow. MitraClip was performed 2 weeks after Impella, and functional mitral regurgitation improved from severe to mild, and Impella was removed on the same day. Inotropes could be ceased, and he was discharged 2 months after MitraClip. Discussion : During inotrope-dependent status, there was a risk that HF would worsen with haemodynamic collapse when performing CRT implantation, and we firstly supported his haemodynamics by Impella. Cardiac resynchronization therapy implantation before MitraClip seemed to be crucial. In fact, the mitral valve morphology before Impella insertion had very poor coaptation of the anterior and posterior leaflets that was not optimal for MitraClip procedure. But the Impella support and correction of dyssynchrony by CRT markedly improved the coaptation of those leaflets. The combination therapy of CRT and MitraClip unloading with Impella maybe a new therapeutic option for advanced HF.